Draft Genome Sequence of a Methicillin-Resistant Staphylococcus aureus ST1413 Strain for Studying Genetic Mechanisms of Antibiotic Resistance - Marasa, Bernard S. (American Society for Microbiology, 2014)
Here we report the whole draft genome sequence of a methicillin-resistant Staphylococcus aureus ST1413 strain. Determining the distribution and arrangement of various genes associated with drug resistance, toxicity, and diseases will enhance our understanding about its adaptability to thrive in different ecological niches and help in the development of effective treatments for enterotoxigenic staphylococcal infections.